Agostino De Rosa (a cura di). Roma anamorfica. Prospettiva e illusionismo in epoca barocca (diségno, 2019)
The book Roma anamorfica. Prospettiva e illusionismo in epoca barocca, edited by Agostino De Rosa, has recently been published by Aracne. It contains eighteen essays by scholars of different disciplines on the subject of anamorphic projection, a sophisticated intellectual game that takes perspective to its ultimate consequences by applying the method literally in what we could call ‘extreme’ projective conditions. The book also has an extensive bibliography and short biographies about the authors. (read more)